TDO structure investigation in aqueous solution by TOF-MS, UV, Raman and quantum chemistry calculations. (4th July 2019) - Shao, Jianzhong; Liu, Xiaoyun; Makarov, Sergei V.; Pei, Kemei
ABSTRACT: Time of flight-mass spectroscopy (TOF-MS), ultraviolet (UV) absorption and Raman spectroscopy, and quantum chemistry calculations were used to investigate the thiourea dioxide (TDO) structure in aqueous solution. TOF-MS with the direct injection sample method was used to get molecular weight information of TDO in solution. The two structural models, (NH2 )2 CSO2 (I) and NH2 NHCSO2 H (II), were used for the TDO single molecule, and all the methods lead to a consistent conclusion that TDO water solution is a mixture of In-cyc clusters (cyclic structures containing n molecules of TDO) and II single molecule. This work reveals the existence state of TDO in aqueous solution and supplies systematic method to explore the molecular structure of liquid solution. GRAPHICAL ABSTRACT: